Biofuels and biodiversity in South Africa - Ryan Blanchard; David Richardson; Patrick O'Farrell; Graham von Maltitz (South African Journal of Science, 2011)
The South African government, as part of its efforts to mitigate the effects of the ongoing energy crisis, has proposed that biofuels should form an important part of the country's energy supply. The contribution of liquid biofuels to the national fuel supply is expected to be at least 2% by 2013. The Biofuels Industrial Strategy of the Republic of South Africa of 2007 outlines key incentives for reaching this target and promoting the development of a sustainable biofuels industry. This paper discusses issues relating to this strategy as well as key drivers in biofuel processing with reference to potential impacts on South Africa's rich biological heritage. Our understanding of many of the broader aspects of biofuels needs to be enhanced. We identify key areas where challenges exist, such as the link between technology, conversion processes and feedstock selection. The available and proposed processing technologies have important implications for land use and the use of different non-native plant species as desired feedstocks. South Africa has a long history of planting non-native plant species for commercial purposes, notably for commercial forestry. Valuable lessons can be drawn from this experience on mitigation against potential impacts by considering plausible scenarios and the appropriate management framework and policies. We conceptualise key issues embodied in the biofuels strategy, adapting a framework developed for assessing and quantifying impacts of invasive alien species. In so doing, we provide guidelines for minimising the potential impacts of biofuel projects on biodiversity.